Quiz Bell Design using NodeMCU ESP8266 for Quiz Contest at IAIN Pontianak - Havizul, Havizul; Zulkarnain, Zulkarnain (Jurnal Edukasi Elektro, 2023)
Quiz Buzzer is one of important elements in a quizz contest. In Tadris Matematika Study Program's Birthday event, one of contest held is quiz contest for High School Student in Kalbar Province. Hereby, author is going to design the buzzer circuit which is able to be used in that quiz contest. This circuit was build by some components, namely push button, buzzer, indicating light, transistor switching circuit for driving the buzzer and indicating light, and a NodeMCU ESP8266 as the system controller. Design of hardware was conducted by referring to literature studies, basic theory, and datasheet. Testing of developed codes was conducted over the Quiz Buzzer Protoyping that is assembled on the breadboard. Testing results showed that the quiz buzzer circuit working properly as needed and the design of 3 teams quiz buzzer.